Stimuli-responsive supramolecular hydrogels for paclitaxel delivery: Progress and prospects - Mohammad Qutub; Amol Tatode; Jayshree Taksande; Tanvi Premchandani; Milind Umekar; Ujban Md Hussain; Dinesh Biyani; Dadaso Mane (Aspects of Molecular Medicine)
Cancer remains a leading cause of death worldwide, while chemotherapy playing a pivotal role in its management. However, traditional chemotherapy often encounters challenges such as non-specific drug delivery, systemic toxicity, and rapid clearance. Thermosensitive supramolecular hydrogels have emerged as an innovative platform for localized and sustained drug delivery, particularly for paclitaxel (PTX), a potent chemotherapeutic agent. These hydrogels exhibit unique sol-gel phase transitions at physiological temperatures, enabling minimally invasive administration and prolonged retention at tumor sites. Advances in hydrogel formulations, including dual stimuli-responsive systems and nanocrystal-loaded designs, enhance drug stability, controlled release, and therapeutic efficacy. Additionally, these hydrogels can incorporate multimodal therapeutic agents, such as immunomodulators and photosensitizers, achieving synergistic anticancer effects. Despite significant progress, challenges remain in optimizing tumor penetration, scaling production, and addressing tumor heterogeneity. Ongoing research into hydrogel composition, biocompatibility, and targeted delivery mechanisms aims to overcome these limitations, paving the way for their clinical translation. This review highlights recent advancements and future prospects of thermosensitive hydrogels for PTX delivery, emphasizing their potential to revolutionize cancer treatment by reducing systemic toxicity and improving localized therapeutic outcomes.